The Development of The Flows of Educational Philosophy: Theoretical Concept and Implementation in 21st-Century Learning - Dwi Yuniasih Saputri; Sunardi Sunardi (Universitas Sebelas Maret, 2023)
The purpose of writing the article is to analyze the development of the flow of educational philosophy: theoretical concepts and implementation in 21st-century learning. This is a systemic literature review. The literature finding was done through the Semantic Scholar database and book review with the topic of the development of education flow and its implementation. Each education has a different view of human development. This is based on the dominant factors that serve as the basis for human development. The implementation in education can be seen from several aspects, including the meaning of education, education goals, curriculum, learning, and the role of teachers in learning. The result of the research is that understanding the flow of education is very important when an educator or teacher wants to keep abreast of educational developments. The result of this thinking is called the flow or new education movement. The flow/movement affects education around the world, including in Indonesia. The philosophy of education can determine the learning process such as determining models, methods, strategies, and evaluation in learning. It cannot be said that one flow is better than another because its use is adjusted to the level of need, current situation, and conditions. The research concludes that each flow has its principles. Three flows influence human development, namely (1) Nativism, this flow states that human development is influenced by innate factors from birth. (2) Empiricism states that human development is caused by environmental factors. (3) Convergence states that human development is influenced by the interaction between the carrier and the environment.